Perencanaan Sequence Penambangan Batubara Triwulan 1 Tahun 2022 PT. Bima Putra Abadi Citranusa, Desa Lubuk Betung, Kecamatan Merapi Selatan, Kabupaten Lahat, Provinsi Sumatera Selatan - Firdaus Firdaus; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2023)
Production at PT. Bima Putra Abadi Citranusa, especially in the 4th quarter of 2021, has not yet reached the production target for both overburden stripping and coal getting. The production target was not achieved because the mining stage design at the company had not been maximized. For this reason, it is necessary to plan a mining sequence in the first quarter of 2022 to catch up with the production target. Data processing was carried out using the Minescape 5.7 software and Microsoft Office 2019. The result was a stripping ratio of 3.87 in the first quarter of 2022 with a plan for mining stages to be carried out mostly on the low wall section so that as much as 2,361,610 BCM of overburden can be produced. coal 609,840.23 tons. The digging equipment used is the Caterpillar 345 EXCZ Excavator, the Doosan 520 EXZ Excavator and the Doosan 800 EXCZ Excavator while the transport equipment used is the Hino 500 DTB dump truck, Mercy Axor DTMB, Hino 700 DTM and Terex TR50D.